Association between Macrophage’s Cell Number and Maternal Factors in Human Milk - Khudri, Ghaniyyatul; Sukmawati, Dewi; Barasila, Atikah Chalida; Suryandari, Dwi Anita (Makara Journal of Science, 2024)
Infant nutrition and immune protection require the consumption of human milk, with macrophages mainly contributing to immune defense and infant development. This study was performed to investigate the correlation between macrophage cell numbers in human milk and various maternal factors. Thirteen human milk samples were collected from lactating mothers and were evaluated for macrophage cell numbers using a hemacytometer. The recorded questionnaire containing several questions, including age, multivitamin consumption, coronavirus disease 2019 vaccination status, allergy history, and lactation duration, was used to determine the maternal factors. Pearson’s correlation and Mann-Whitney test was employed in statistical analysis, with p-values < 0.05 considered significant. The macrophage cell number reached 54.236 ± 7.456 cells per mL. Notably, a significant correlation was observed between maternal allergy history and the number of macrophage cells in human milk (p = 0.049). Meanwhile, no statistically significant associations were detected among multivitamin consumption (p = 0.833), vaccination status (p = 0.923), and lactation duration (p = 0.236). This study emphasizes the effect of maternal characteristics on the composition and immune properties of human milk. The specific mechanisms underlying these correlations and their potential influence on infant health and development must be explored in future research.